Pengaruh Gaya Kepemimpinan, Motivasi, dan Kompensasi Terhadap Kinerja Karyawan Pada PT PLN Icon Plus SBU Regional Bagian Jawa Timur (Surabaya) - Bagastya Budi Prakoso; Bowo Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research is intended to test and see the influence of Leadership Style, Motivation, Compensation on Employee Performance at PT PLN Icon Plus SBU Regional East Java. The data used in this research is primary data from questionnaires distributed to respondents. Data processing uses Partial Least Square analysis techniques with Structural Equation Model-Partial Least Square (SEM-PLS) as a statistical analysis tool. The results of this research found that Leadership Style, Motivation, Compensation have a positive effect on Employee Performance.